Peaceful co-existence among adherents of Abrahamic faith - Solihin, Sohirin Mohammad (2010)
The research explores the divine principles to maintain peace and harmonious lives across races and religious boundaries in community. It deals in the first part on the concept and purpose of dialogue and practical example during the live time of the Prophet Muhammad (pbuh) and later generations how they demonstrated peaceful co-existence with the non-Muslims. The presence of other religious followers in Arabia and its surrounding areas is also dealt. It studies the concept of pluralism and the wisdom behind existence of diversity of religious adherents in the community. Then, it will analyze the views and commentary of Muslim exegetes and how they deal with religious text. This is mainly related with methodological approach which they develop in giving the commentary. Moreover, it analyzes the current trend of making religious equality, perception of pluralism in the hands Western scholars, the purpose and practice of interfaith dialogue and its implication which is mainly aimed at reducing religious fervor among Muslims.